MELT POLYMERIZATION OF HEXACHLOROCYCLOTRIPHOSPHAZENE IN THE PRESENCE OF ORGANOTIN(IV) COMPOUNDS - CHO, YH; SOHN, YS; JUN, MJ (JOHN WILEY & SONS INC, 1993)
The melt polymerization of hexachlorocyclotriphosphazene to poly (dichlorophosphazene) has been studied in the presence of organotin (IV) compounds. Unlike other typical Lewis acids, diethyltin(IV) chloride, Et2SnCl2, has shown to be an inhibitor for the thermal polymerization of the trimer, raising the activation energy to 70 kcal/mol. Diethyltin (IV) chloride remarkably delayed the rate of polymerization and efficiently inhibited the cross-linking reaction, thus leading to an improvement in the yield of the linear polymer without sacrifice to its molecular weight. (C) 1993 John Wiley & Sons, Inc.
Keywords: SERIES